The Influence of Information and Communication Technology Development and Regional Minimum Wage on Gross Domestic Regional Product in North Maluku Province - Situmorang, Frandika; Suharianto, Joko (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to analyze the influence of information and communication technology development and minimum wage policies on economic growth in North Maluku Province. As an archipelagic region, North Maluku faces geographical challenges in the form of limited accessibility and inequality of development between regions. In recent years, local governments have encouraged the acceleration of development, especially in the information and communication technology sector and the establishment of a minimum wage policy. This study uses a quantitative approach with multiple linear regression methods, utilizing secondary data for the period 2012-2024 sourced from the Central Statistics Agency. The variables used include the Information and Communication Technology Development Index (ICT-DI) and the Regional Minimum Wage (RMW) as independent variables, as well as Gross Regional Domestic Product (GDP) as dependent variables. The results of the study show that ICT-DI has a positive and significant effect on GDP, while RMW has a positive but insignificant effect. Simultaneously, both variables have a significant effect on GDP with high explanatory ability. This indicates that increased access and utilization of technology has an important role in driving economic activity, while minimum wage policies have not had a real impact. Thus, strengthening digital development is a key factor in encouraging sustainable economic growth in the archipelago.